2018
DOI: 10.1021/acs.jctc.7b01159
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy Calculations of Membrane Permeation: Challenges Due to Strong Headgroup–Solute Interactions

Abstract: Understanding how different classes of molecules move across biological membranes is a prerequisite to predicting a solute's permeation rate, which is a critical factor in the fields of drug design and pharmacology. We use biased molecular dynamics computer simulations to calculate and compare the free energy profiles of translocation of several small molecules across 1,2-dioleoyl- sn-glycero-3-phosphocholine (DOPC) lipid bilayers as a first step toward determining the most efficient method for free energy cal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 72 publications
3
48
1
Order By: Relevance
“…For a fully quantitative description, it has become fundamental to predict the kinetic behaviour of drugs addressing membrane interaction and permeation. 1,[5][6][7][8] Studies related to the transport of small ligands crossing various phospholipid membranes are the subject of increased interest in recent years 5, [9][10][11][12][13] . There are also significant challenges to investigating this behaviour experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a fully quantitative description, it has become fundamental to predict the kinetic behaviour of drugs addressing membrane interaction and permeation. 1,[5][6][7][8] Studies related to the transport of small ligands crossing various phospholipid membranes are the subject of increased interest in recent years 5, [9][10][11][12][13] . There are also significant challenges to investigating this behaviour experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, MSMs allow for the convenient combination of multiple MD trajectories into a single kinetic network model from which experimental observables and kinetic rates can be computed. 6,13,[26][27][28] Using experimentally obtained permeabilities by Eyer et al 14 across a lipid membrane for seven structurally unrelated drugs (Fig. 2), Dickson et al 29 recently demonstrated that accurate results for the permeability rates can be obtained by running long unbiased MD simulations 29 .…”
Section: Introductionmentioning
confidence: 99%
“…However, our calculations suggest that the PMF trends are similar for pVEC and del5 pVEC systems (Figure ). Both peptides exhibit a local free energy minimum when they are at the lipid‐water interface, which is a common property observed for hydrophilic solutes that prefer to reside either in bulk water or the water‐lipid interface, a highly sensitive region in the free energy calculation studies of peptide insertion . The energetic cost of carrying a single pVEC into the bilayer core is around 92 kcal/mol, while this value is 62 kcal/mol (Figure ) for del5 pVEC.…”
Section: Resultsmentioning
confidence: 95%
“…During these SMD simulations, pulling of the peptide may have induced the formation of the water pore, which is stable for tens or hundreds of nanoseconds, and this in turn makes it challenging to converge to an equilibrium PMF, as discussed in previous peptide translocation studies . The convergence of free energy profiles can be verified by checking the symmetry of the free energy profiles (with respect to the bilayer center), and the exhibition of a plateau region around the center of the bilayer . Furthermore, it was reported that even with sampling times that exceeded 20 microseconds, it was still not possible to obtain a fully converged free energy profile for CPP insertion .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation